Armazenamento a frio de ramos porta-borbulhas e métodos de enxertia de cultivares de marmeleiro - Celant, Viviane Marcela; Pio, Rafael; Chagas, Edvan Alves; Alvarenga, Ángelo Albérico; Dalastra, Idiana Marina [UNESP]; Campagnolo, Marcelo Angelo (My University, 2010)
In order to increase the use of propagation material, enlarge the offer period of the quince seedlings production and dynamic use of the labor in the nursery, it becomes necessary to store the of budsticks. Thus, the present research aimed to study the feasibility of the maintaining budstick of different quince cultivars, through cold storage and to verify the grafting method to promote better development of the graft. Branches of the 'Japonês' (Chaenomeles sinensis), 'Smyrna', 'Portugal', 'Mendoza Inta-37' and 'Provence' (Cydonia oblonga) quince cultivars were collected in July, 2008. One of the branches was used for grafting (methods budding and cleft grafting methods) in 'Japonês' rootstock seedlings of six months of age and other part was stored at e low temperature (wrapped up cutting in humidified paper and wrapped up in polyethylene sacks, placed in cold chamber for 4°C) for 30 and 60 days. After 60 days, the percentage of sprouting was measured and 120 days after grafting, the length, diameter and mass dries average of the grafts were measured. It was concluded that, despite the cultivars presented anydifference, it is recommended that the branches need to be stored for up to 30 days, if the cleft grafting is used.
Cold storage of budsticks and grafting methods of quince cultivars
Keywords: Chaenomeles sinensis; Cydonia oblonga; Seedlings production